Field data implicating Culicoides stellifer and Culicoides venustus (Diptera: Ceratopogonidae) as vectors of epizootic hemorrhagic disease virus - McGregor, Bethany L. (Parasit Vectors, 2019)
BACKGROUND: Epizootic hemorrhagic disease virus (EHDV) is an Orbivirus of veterinary importance which is transmitted by biting midges of the genus Culicoides (Diptera: Ceratopogonidae) to ruminants. Culicoides sonorensis Wirth & Jones, the only confirmed vector of EHDV in the USA, is rare in the southeastern states where transmission persists, suggesting that other Culicoides species transmit EHDV in this region. The present study aimed to determine which Culicoides species transmitted EHDV in Florida and Alabama, two states in the southeastern USA. Viral RNA was detected in field-collected midges using molecular methods. These data are presented alongside data on Culicoides blood meal analysis, white-tailed deer (Odocoileus virginianus) aspiration, and seasonality to demonstrate an interaction between potential vector species and EHDV hosts. RESULTS: Out of 661 pools tested, 20 pools were positive for EHDV viral RNA, including six pools from Culicoides stellifer (Coquillett) and 14 pools from Culicoides venustus Hoffman. The overall infection rate was 0.06% for C. stellifer and 2.18% for C. venustus. No positive pools were identified for a further 17 species. Serotypes identified in Culicoides included EHDV-2, EHDV-6, and coinfections of EHDV-2 and EHDV-6 and were identified in similar proportions to serotypes in deer at 3 of 4 deer farms. Viral detections conducted in Alabama also identified one positive pool of C. venustus. Blood meal analysis revealed that both Culicoides species fed on white-tailed deer (verified through aspiration), fallow deer, and elk, species for which EHDV viremia has been documented. Seasonality data indicated that both species were present throughout the period in which viral transmission occurred to EHDV hosts in 2016 in addition to the 2017 epizootic. CONCLUSIONS: Our finding of EHDV positive pools of field-collected C. stellifer and C. venustus and an interaction between these species and EHDV hosts satisfy two of the four criteria for vector incrimination as set by the World Health Organization. Determining the vectors of EHDV is an important step towards developing sound strategies for the control of vector Culicoides and management of EHDV in the southeastern USA.